Intestinal Microbiota and Gene Expression Alterations in Chinese Mitten Crab (Eriocheir sinensis) Under Deltamethrin Exposure - Chunyi Zhong; Jinliang Du; Haojun Zhu; Jiancao Gao; Gangchun Xu; Pao Xu (Antioxidants)
The intestine is an important immune organ of aquatic animals and it plays an essential role in maintaining body health and anti-oxidative stress. To investigate the toxic effects of deltamethrin in intestinal tissue of Chinese mitten crabs (Eriocheir sinensis), 120 healthy crabs were randomly divided into two experimental groups (blank control group and deltamethrin-treated group), with three replicates in each group. After being treated with deltamethrin for 24 h, 48 h, 72 h, and 96 h, intestinal tissues were collected aseptically to assess the effects of deltamethrin on oxidative stress, immunity, apoptosis-related genes, and the structure of microflora in intestinal tissues. Additionally, correlations between gut microbiota composition and intestinal tissue damage-associated genes were analyzed. The results demonstrated that prolonged exposure to deltamethrin induced oxidative stress damage in intestinal tissue. Compared with the blank control group, the expression of autophagy-related genes B-cell lymphoma/Leukemia-2 (bcl-2), c-Jun N-terminal kinase (jnk), Microtuble-associated protein light chain 3 (lc3c), Cysteine-dependent Aspartate-specific Protease 8 (caspase 8), BECN1(beclin1), oxidative stress damage-related genes MAS1 proto-oncogene (mas), Glutathione Peroxidase (gpx), kelch-like ECH-associated protein 1 (keap1), Sequestosome 1 (p62), Interleukin-6 (il-6), and immune-related genes Lipopolysaccharide-induced TNF-alpha Factor (litaf), Heat shock protein 90 (hsp90) and prophenoloxidase (propo) in the deltamethrin treatment group were significantly up-regulated at 96 h (p < 0.05 or p < 0.01). Additionally, 16S rRNA sequencing showed that the diversity of intestinal flora in the deltamethrin-treated group was significantly higher compared with the blank control group (p < 0.01). Analysis of the differences in the composition of intestinal flora at the genus level showed that the relative abundance of Candidatus Bacilloplasma in the deltamethrin treatment group was significantly lower than that in the blank control group (p < 0.01). In contrast, the relative abundances of Flavobacterium, Lachnospiraceae_NK4A136_group, Acinetobacter, Chryseobacterium, Lacihabitans, Taibaiella, Hydrogenophaga, Acidovorax, and Undibacterium were significantly higher than those in the blank control group (p < 0.05 or p < 0.01). Pearson correlation analysis revealed that Malaciobacter, Shewanella, and Prevotella exhibited significant positive correlations with gene indicators (jnk, gpx, lc3c, litaf, hsp90), while Dysgonomonas, Vibrio, and Flavobacterium demonstrated significant negative correlations with multiple gene indicators (caspase 8, p62, il-16, keap1, jnk, etc). These results demonstrate that deltamethrin significantly impacts the gut microbiota, immune function, and antioxidant capacity of E. sinensis. The changes in gut microbiota have correlations with the biomarkers of intestinal tissue injury genes, indicating that gut microbiota plays a crucial role in deltamethrin-induced intestinal tissue damage. These insights contribute to a better understanding of the ecological risks associated with deltamethrin exposure in aquatic organisms.